A conceptual framework toward identifying and analyzing challenges to the advancement of pharmacy - Bader, Lina R.; McGrath, Simon; Rouse, Michael J.; Anderson, Claire (Elsevier, 2016)
Background: Pharmacists and healthcare professionals are faced with increasing and changing health care needs around the world. In order to meet these demands, they are required to continuously upgrade and develop their professions. Reprofessionalization drives are therefore crucial to the successful delivery of health services, but traditional theories of the professions provide little practical guidance to evaluating the overall status of a profession.